2000
DOI: 10.1093/jnci/92.21.1764
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Tobacco Carcinogen-Induced DNA Adducts and Lung Cancer Risk: a Molecular Epidemiologic Study

Abstract: Background: Only a fraction of cigarette smokers develop lung cancer, suggesting that people differ in their susceptibility to this disease. We investigated whether differences in DNA repair capacity (DRC) for repairing tobacco carcinogen-induced DNA damage are associated with differential susceptibility to lung cancer. Methods: From August 1, 1995, through April 30, 1999, we conducted a hospital-based, casecontrol study of 316 newly diagnosed lung cancer patients and 316 cancer-free control subjects matched o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(61 citation statements)
references
References 46 publications
4
56
0
Order By: Relevance
“…Compared to exposure to these carcinogens, the effect of the -572G/C polymorphism must be relatively weak in smokers. Other risk factors, such as reduced DNA repair capacity among smokers (Wei et al, 2000) might also contribute to this disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to exposure to these carcinogens, the effect of the -572G/C polymorphism must be relatively weak in smokers. Other risk factors, such as reduced DNA repair capacity among smokers (Wei et al, 2000) might also contribute to this disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, others have found that, when compared to unaffected individuals, patients with lung cancer were characterized by higher rate of spontaneous chromosomal aberrations 11 , elevated endogenous single stranded breaks 12 , higher sensitivity to gamma-radiation, bleomycin, and BPDE 12–14 ,, and lower DNA repair capacity 15 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiological studies in which a variety of global measures of DNA repair capacity were used found that individuals with lung cancer displayed a higher rate of spontaneous and carcinogen-induced chromosomal aberrations than the healthy controls 11–14 . Similarly, patients with lung cancer displayed a lower DNA repair capacity than controls 13,15 , which in the presence of a deficient cell cycle checkpoint increased the risk for developing lung cancer even further 14 . Paz-Elizur et al evaluated a more specific aspect of repair.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach also demonstrated an association between lower DRC and the risk of prostate and breast cancers [106,107]. This DRC assay also detected low-level DRC that is responsible for elevated risk of tobacco-induced lung cancer [108] and head and neck cancer [109]. In these experiments, a tobacco carcinogen, benzo[a]pyrene diol epoxide, was used to form DNA adducts on the expression vector that was transfected into the host cells.…”
Section: Overcoming Barriers To Personalized Preventionmentioning
confidence: 97%